Challenges and motivators to physical activity faced by retired men when ageing: a qualitative study - Ebba Langum Bredland; Sylvia Söderström; Kjersti Vik (BMC, 2018)
Abstract Background Active ageing reflects the message from World Health Organisation about addressing the challenge faced by the rapidly ageing population. Knowledge about barriers and facilitators to an active lifestyle must be given more attention. In addition, men seem to participate less in cultural activities and less in fall-prevention groups than women do. When mostly women work with the elderly in primary care, one might question whether the activities offered to older men meet their activity preferences. The aim of this study is to provide new knowledge about challenges and motivators encountered by retired men in maintaining physical activity when ageing. Methods Nine retired men, aged between 66 and 83, wrote a Time Geographic Diary for 7 days each. Two focus group discussions with the men were held. A Systemic Text Condensation was used to analyse the data. Results The analyses identified three categories to describe challenges in being physical active: differences between men and women; meaningful physical activity; and environmental - especially socio-cultural - constraints. Motivating conditions were seen as: new activities to get younger friends, and more information about how to cope. Conclusions To achieve the aim of active ageing, service providers as well as local authorities need to have a better understanding of the challenges retired men encounter when ageing. This study highlights vital aspects of the challenges faced by retired men in maintaining their physical activity level.